2020
DOI: 10.1111/nep.13788
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐transplant biopsy on 5‐year outcomes of expanded criteria donor kidney transplantation

Abstract: Aim: Compared to Standard Criteria Donors (SCD), Expanded Criteria Donor (ECD) kidneys are associated with poorer outcomes, although pre-transplant biopsy may mitigate risks. This study assessed 5-year outcomes of deceased-donor kidney transplant recipients, comparing recipients of ECD allografts evaluated histologically to recipients of SCD and ECD kidneys assessed clinically. Methods: This is a single-centre retrospective study. From November 2005 to December 2009 (Era 1), donors were assessed clinically for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The reports are both suggestive that machine-learning algorithms (artificial intelligence) applied to pre-transplant data may predict the likelihood of gaining eGFR-1, possibly similar to that observed after LDKT. There is additional data beyond KDPI variables available within the OPTN database, including renal volume/mass ( 30 , 31 ), donor biopsy ( 32 , 33 ), (hypo)perfusion parameters ( 34 ), pump ( 35 ), and ischemia characteristics ( 36 ), that may improve the predictive capacity for post-transplant renal function.…”
Section: Discussionmentioning
confidence: 99%
“…The reports are both suggestive that machine-learning algorithms (artificial intelligence) applied to pre-transplant data may predict the likelihood of gaining eGFR-1, possibly similar to that observed after LDKT. There is additional data beyond KDPI variables available within the OPTN database, including renal volume/mass ( 30 , 31 ), donor biopsy ( 32 , 33 ), (hypo)perfusion parameters ( 34 ), pump ( 35 ), and ischemia characteristics ( 36 ), that may improve the predictive capacity for post-transplant renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the most crucial factor is how the histopathological results correlate with long-term graft survival. Many studies have attempted to address the predictive value of renal biopsy with respect to graft outcomes, but the results of these studies have been predominantly inconclusive [20][21][22][23]. For instance, Traynor et al, conducted a retrospective study that examined kidney transplants over a 10-year period to determine whether pretransplant histology is able to predict graft outcomes at 5 years, and whether donor histology adds incremental data to the current clinical parameters.…”
Section: Biopsymentioning
confidence: 99%
“…While the results of these reports suggest that that histological assessment adds little additional prognostic information aside from clinical parameters [20], Yap et al, found that the histological evaluation of ECD kidneys was associated with improved long-term graft survival. Their results suggest that pretransplant biopsy assessment can enable ECD kidneys to be used as a safe and viable option during persistent shortages of kidney donors [21]. The divergence between recent studies highlights the need for a prospective controlled trial to evaluate the predictive value of pretransplant biopsies.…”
Section: Biopsymentioning
confidence: 99%
“…[ 4 ] Despite no agreement has been reached on the “best” grading system for preimplantation biopsies,[ 5 6 7 8 ] from that publication, the Remuzzi–Karpinski score has been widely adopted. [ 9 10 ] Although preimplantation biopsy may generate data for accepting or rejecting an organ, it represents a controversial issue. The major issue that undermines the reliability of histopathology is the low rate of agreement between pathologists on the Remuzzi–Karpinski score.…”
Section: Introductionmentioning
confidence: 99%